Pre-digestion to enhance volatile fatty acids (VFAs) concentration as a carbon source for denitrification in treatment of liquid swine manure. Issue 10 (24th August 2018) - Wu, Sarah (Xiao); Chen, Lide; Zhu, Jun; Walquist, McKenzie; Christian, David
ABSTRACT: Insufficient denitrification in biological treatment is often a result of the lack of a carbon source. In this study, use of the volatile fatty acids (VFAs) generated via pre-digestion as a carbon source to improve denitrification in sequencing batch reactor (SBR) treatment of liquid swine manure was investigated. The pre-digestion of swine manure was realized by storing the manure in a sealed container in room temperature and samples were taken periodically from the container to determine the VFA levels. The results showed that after 14 days of pre-digestion, the VFA level in the digested liquid was increased by 200%. A polynomial relationship for the VFA level in the digested manure with the digestion time was observed with a correlation coefficient being 0.9748. Two identical SBRs were built and operated on 8-h cycles in parallel, with one fed with pre-digested and the other raw swine manure. There were five phases included in each cycle, i.e., anaerobic (90 min), anoxic (150 min), anoxic/anaerobic (90 min), anoxic/aerobic (120 min), and settle/decant (30 min), and the feeding was split to 600 mL/200 mL and performed at the beginning of and 240 min into the cycle. The SBR fed on pre-digested swine manure achieved successful denitrification with only 0.35 mg/L nitrate left in the effluent, compared to 15.9 mg/L found in the effluent of the other SBR. Nitrite was not detected in the effluent from both SBRs. The results also indicated that there was no negative impact of feeding SBRs with the pre-digested liquid swine manure for treatment on the removal of other constituents such as total solids (TS), volatile solids (VS), suspended solids (SS), volatile suspended solids (VSS), and soluble chemical oxygen demand (COD). Therefore, anaerobic digestion as a pretreatment can be an effective way to condition liquid swine manure for SBR treatment to achieve sufficient nitrate removal.